Justification Of Urine Culture Before Transurethral Resection Of The Prostate Gland: Clinical Feasibility And Optimization Of Preoperative Preparation - Magomedrasulovna, Adieva Aminat; Kamalovich, Ziyavutdinov Dzhamaludin; Rustamovich, Shahbanov Murad; Akhmedovich, Abdulpatakhov Ramazan; Khabibullaevna, Musalaeva Aminat; Balguevna, Balgueva Patima; Absalamovich, Umarov Ilyas; Shamilevich, Magomedov Gadzhimurad; Abakarovna, Omarova Madina; Gaziеvna Sullaeva Milana; et al. (Journal of Neonatal Surgery, 2025)
In this work, the clinical expediency of conducting microbiological urine culture before transurethral resection of the prostate gland (TURP) was investigated in patients with benign prostatic hyperplasia. The study included 75 patients divided into two groups: the main group with urine culture and targeted antibacterial therapy, as well as a control group with empirical prophylaxis without pre-sowing. The data obtained showed a high incidence of asymptomatic bacteriuria (44.7%) and significant antibiotic resistance of microorganisms, mainly Escherichia coli. The use of seeding results made it possible to reduce the incidence of postoperative infectious complications from 24.3% to 7.9%, as well as reduce the duration of hospitalization and reduce the need for repeated therapy. The results of the study confirm the importance of microbiological control of urine as a key stage of preoperative preparation for TURP, which contributes to improving the safety of surgical treatment and improving clinical outcomes.